Validation of self-reported history of root canal treatment in a southern Brazilian subpopulation - Gisele Jung FRANCISCATTO; Bárbara Thereza de Freitas KOPPE; Carolina Bender HOPPE; João Augusto Peixoto de OLIVEIRA; Alex Nogueira HAAS; Fabiana Soares GRECCA; Giampiero ROSSI-FEDELE; Maximiliano Schünke GOMES (Sociedade Brasileira de Pesquisa Odontológica, 2019)
Abstract The aim of this study was to assess self-reported history of root canal treatment (SRHRCT) as a method for detecting the presence of root canal treatment (RCT) and apical periodontitis (AP) in a southern Brazilian subpopulation. In this cross-sectional study, 136 military police officers from the city of Porto Alegre, Brazil, were included. The participants were interviewed and full-mouth periapical radiographs were taken. A calibrated examiner determined the presence of RCT and AP by applying standardized criteria. The diagnostic accuracy of SRHRCT was calculated separately for RCT and AP. Accuracy, sensitivity, specificity, positive and negative predictive values (+PV and -PV), efficiency, and positive and negative likelihood ratios (+LR and -LR) were estimated. The mean age of the participants was 34.1 ± 10.4 years and 88.2% were males. Overall, SRHRCT demonstrated high sensitivity and specificity for RCT, but not for AP: sensitivity (RCT = 0.960, AP = 0.757) and specificity (RCT = 0.835, AP = 0.631). The estimated values for PV and LR were: +PV (RCT=0.777, AP=0.396), -PV (RCT = 0.972, AP = 0.890), +LR (RCT = 5.853, AP = 2.057), and -LR (RCT = 0.046, AP = 0.383). SRHRCT proved to be a good predictor of the presence of RCT, but a weak predictor of AP in this subpopulation.